Effects of an Oroxylum indicum Extract (Sabroxy®) on Cognitive Function in Adults With Self-reported Mild Cognitive Impairment: A Randomized, Double-Blind, Placebo-Controlled Study - Lopresti, Adrian L.; Smith, Stephen J.; Majeed, Muhammed; Drummond, Peter D. (Frontiers in Aging Neuroscience, 2021)
Background: Oroxylum indicum has been used in traditional Ayurvedic medicine for the prevention and treatment of several diseases and may have neuroprotective effects. Purpose: Examine the effects of Oroxylum indicum on cognitive function in older adults with self-reported cognitive complaints. Study Design: Two-arm, parallel-group, 12-week, randomized, double-blind, placebo-controlled trial. Methods: Eighty-two volunteers received either 500 mg, twice daily of a standardized Oroxylum indicum extract or placebo. Outcome measures included several computer-based cognitive tasks, the Control, Autonomy, Self-Realization, and Pleasure scale (CASP-19), Cognitive Failures Questionnaire, and the Montreal Cognitive Assessment (MoCA). Changes in the concentration of brain-derived neurotrophic factor (BDNF) were also examined. Results: Compared to the placebo, Oroxylum indicum was associated with greater improvements in episodic memory on several computer-based cognitive tasks such as immediate word recall and numeric working memory, and a faster rate of learning on the location learning task. However, there were no other significant differences in performance on the other assessed cognitive tests, the MoCA total score, or other self-report questionnaires. BDNF concentrations increased significantly in both groups, with no statistically-significant between-group differences. Oroxylum indicum was well tolerated except for an increased tendency for mild digestive complaints and headaches. Conclusion: The results of this first human trial on the cognitive-enhancing effects of Oroxylum indicum suggest that it is a promising herbal candidate for the improvement of cognitive function in older adults with self-reported cognitive complaints.